Difficulties and Countermeasures in Hospital Emergency Management for Fast-Lane Treatment of Acute Stroke During the COVID-19 Epidemic Prevention and Control - Yang, Haojun; Chen, Zhuohui; Fan, Yishu; Xiang, Lan; Hu, Xinhang; Wu, Tong; Xiao, Bo; Feng, Li; Zhao, Zhihong; Chi, Yunfang; Zhang, Mengqi (Frontiers in Neurology, 2020)
Background: Coronavirus disease 2019 (COVID-19) has a long incubation period and a high degree of infectivity. Patients may not show specific signs or symptoms of upper respiratory tract, and the age at onset is similar to that of stroke. Furthermore, an increase in neurological conditions, specifically acute cerebrovascular disease, has been detected. Providing emergency treatment for acute stroke in accordance with the strict epidemic control measures is currently one of the main challenges, which is rapid onset and a major cause of death and disability globally. We aimed to evaluate the emergency treatment system for acute stroke during the epidemic control period to provide a reference and basis for informing government and medical institutions on improving patient treatment rates during this period. Methods: Difficulties faced in providing emergency treatment for stroke during an epidemic were investigated and combined with medical educational resources and clinical management experiences to construct an emergency treatment framework for acute stroke during the epidemic control. Findings: Currently, emergency treatment measures for acute stroke during the epidemic control period are limited because the main focus is on identifying COVID-19 comorbidities during the critical period. Establishing standards for patients in the neurological outpatient consultation rooms and emergency observation and resuscitation zones; implementing a fast lane system for the emergency treatment of patients with acute stroke and strengthening ward management and medicine popularisation can improve the treatment efficiency for stroke patients during the epidemic and provide a reference for peers in clinical practice. Interpretation: Emergency treatment for acute stroke during COVID-19 epidemic control period requires a joint promotion of clinical, popularisation, and teaching resources.